Planning special physical training for rowers in China: a randomized study - Kong, X.; Guo, P.; Wang, W.; Rusanova, O.; Diachenko, A. (Journal of Physical Education and Sport, 2020)
Purpose: It is considered that the use of training approche for special physical training in the conditions of latent (compensated) fatigue is a necessary condition for increasing the special performance of rowers throughout the second half 2000 m racing distance. Of particular relevance is the implementation of this approach in rowing, where a high level of special performance of athletes with the development of fatigue during the racing distance is one of the key factors for achieving high sports results. Participants. The study included the leading rowers of the province - members and candidates for Shandong provincial rowing team. Total - 40 man athletes at the age from 18 to 23 years. Studies were conducted in the water sports centre of Shandong Province (China) during the competition period. Results: These data indicate that the increase in the effectiveness of competitive activity has resulted from an increase in the special performance of rowers in the second half of the course during the period of hidden (compensated) fatigue. There is reason to believe that one of the factors for increasing the special performance in the second half of the distance is the use of the training effects system presented in the work, including exercise groups, where the parameters for determining the work parameters were strictly individual and resulted from monitoring the functional support of the special rowers in developing fatigue typical of the second half of the competition distance. In the process of controlling the passage of the competition distance, the time to throughout the 1000-1500 m, 1500-2000 m and the entire distance trail decreased by 2.9 ± 0.2 s, 4.2 ± 0.3 s, 7.1 ± 0.4 s in the process of overcoming the 2000 m racing distance in the natural conditions of training.